Correlation of peak expiratory flow rate with body mass index in school children of a government school of Kathmandu - Nepal, Archana (Journal of Kathmandu Medical College, 2019)
Background: Peak expiratory flow rate is a reliable data to assess the severity and effectiveness of management in adolescent with asthma. There is no study done in Nepalese children to relate it with the body mass index. The present study tries to find out its relation with age, sex, weight, height, body mass index. Objectives: To identify the effect of body mass index on peak expiratory flow rate among healthyNepalese school children. Methodology: Three hundred and ten students of a government school at Kalimati wereincluded in this study. Highest of the three peak expiratory flow rate readings were recorded using Wright’s peak flow meter. Questionnaire were used to find out the pre-existing disease conditions for exclusion from the study population. Weight and height were measured using standardized instruments and body mass index was calculated using formula: weight (kg)/height2(m). Results: Peak expiratory flow rate initially increased with increasing body mass index from -1SD to +2SD and it declined as body mass index increased above +2SD. Pearson’s correlation r was positive with values of 0.7, 0.65, 0.64, 0.35 for height, weight, age and body mass index respectively. Height had highest positive correlation with peak expiratory flow rate while body mass index though had positive but weak correlation with peak expiratory flow rate. Conclusion: Body mass index is positively correlated with peak expiratory flow rate. However, mean Peak expiratory flow rate initially increases with increasing body mass index and it starts declining as body mass index reaches overweight range.